The Implementation of Character Education as a Solution to Prevent Bullying in Schools - Wiwin Rif’atul Fauziyati; Medina Nur Asyifah Purnama; Lisma Meilia Wijayanti (Civiliza Publishing, Indonesia., 2025)
Bullying is a serious problem that persists in schools and negatively impacts students' psychological and social development, as well as their academic achievement. Bullying prevention efforts require a preventative and sustainable approach, one of which is through the implementation of character education. This article aims to examine the application of character education as a solution to preventing bullying in schools. This research uses a qualitative approach with a literature study method, through a review of various scientific sources such as journals, books, and relevant educational policy documents. The results of the study indicate that character education plays a crucial role in instilling moral values ​​such as empathy, tolerance, responsibility, honesty, and mutual respect, which can significantly reduce bullying behavior. The integrated implementation of character education through classroom learning, school culture, extracurricular activities, and educator role models can create a safe and conducive school climate. Thus, character education can be a strategic and effective solution in efforts to prevent bullying in schools if implemented consistently and sustainably.